A method for preparing a granular size distribution enhanced SiC ceramic

CN122916680APending Publication Date: 2026-10-16SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611360853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,单纯的颗粒级配仍然存在致密度低的缺陷,并且粗颗粒与细颗粒之间的烧结收缩速率不一致,并且界面相容性差,其对于断裂韧性的提升幅度有限;单纯的颗粒级配仅能调控基体颗粒形貌,高温下晶界软化、界面应力释放、高温强度等无明显改善,不能适配超高温的工况

Benefits of technology

1.本发明对碳化硅颗粒进行三级梯度级配,粗颗粒构建刚性骨架,中颗粒和细颗粒填充间隙,降低粉体的原始堆积孔隙,结合聚乙二醇600成分避免颗粒团聚,促进颗粒分散,得到高堆积密度、分散均匀的级配碳化硅粉料,可以从源头降低收缩率,减少大尺寸气孔;在包覆步骤中,金属硝酸盐经过氨水的共沉淀,在碳化硅颗粒表面生成La(OH)3-Hf(OH)4-Zr(OH)4薄膜,经高温煅烧,得到La2O3-HfO2-ZrO2复合氧化物纳米包覆层,其可以大幅降低烧结密度,抑制碳化硅晶粒的异常长大,大幅提升断裂韧性,提升高温稳定性,然后与氮化硼纳米片等助剂成分混合,得到致密的碳化硅陶瓷;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a preparation method of a particle grading reinforced SiC ceramic, and belongs to the SiC ceramic field; the preparation method comprises silicon carbide grading, coating, preparation of a forming powder, forming and calcination; in the coating, hafnium nitrate and zirconium nitrate are added into anhydrous ethanol, stirring is carried out at room temperature for 10-15 min, lanthanum nitrate is added and stirring is continued, and a precursor mixed solution is obtained; the graded silicon carbide is added into the precursor mixed solution, ultrasonic dispersion is carried out for 25-30 min, the temperature is increased to 55-60 DEG C, the pH value is adjusted to 8.5-9.0, stirring reaction is carried out for 2.0-2.3 h, after centrifugation, filtration and washing, drying is carried out, and cooling to room temperature is carried out, and then the coated silicon carbide is obtained by placing into a calcination furnace, calcination under a nitrogen atmosphere at 570-600 DEG C for 2.0-2.2 h, natural cooling to room temperature, and obtaining the coated silicon carbide; the ceramic product obtained by the application has high density, low shrinkage, high strength and excellent high-temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of SiC ceramics, and specifically relates to a method for preparing particle-graded reinforced SiC ceramics. Background Technology

[0002] Silicon carbide (SiC) ceramics are widely used in industrial fields such as machinery manufacturing and petrochemicals due to their excellent resistance to extreme environments, including high temperature strength retention, low density, high hardness, strong oxidation resistance, excellent thermal conductivity and controllable coefficient of thermal expansion. Although silicon carbide ceramics have many advantages, they also have some disadvantages. First, silicon carbide is a compound with highly covalent bonds, a high melting point, a low self-diffusion coefficient, and a low diffusion rate during sintering, making it difficult to form dense ceramic materials during sintering. In addition, silicon carbide ceramics have low fracture toughness at room temperature and are sensitive to defects, resulting in poor mechanical properties, which greatly limits their application in some fields.

[0003] To enhance the densification of ceramics and improve their mechanical properties, existing technologies typically involve adding sintering aids, which mainly include solid-phase sintering aids and liquid-phase sintering aids. Solid-state sintering aids typically include boron systems, boron carbide systems, and carbon systems. Boron segregates grain boundaries to reduce interfacial energy, while carbon reduces silicon carbide to form a silicon dioxide oxide layer on the surface. Densification is achieved at high temperatures through solid-state quantum diffusion. However, the sintering temperature is too high, the energy consumption is extremely high, and the equipment requirements are stringent. Furthermore, high temperatures can easily lead to abnormal grain growth, and larger grain sizes will reduce the fracture toughness of the product. Liquid phase sintering mainly uses a yttrium oxide and alumina additive system, which can generate a low-viscosity liquid phase, accelerate mass transfer, reduce sintering temperature, inhibit grain coarsening at low temperatures, and fill the pores of the green body to increase density. However, excessive additives can introduce a large number of impurity phases, reducing the corrosion resistance of the product. Furthermore, after sintering, a continuous glassy phase exists at the grain boundaries. The thermal expansion coefficient of the glassy phase is mismatched with that of the silicon carbide matrix, resulting in residual internal stress after cooling, which can easily lead to cracks and reduce the fracture toughness of the product.

[0004] Another method involves introducing a second phase as a toughening phase, typically silicon carbide whiskers or carbon fibers. This relies on crack deflection, whisker pull-out, and interface bridging mechanisms to hinder rapid crack propagation and improve the fracture toughness of the product. However, the toughening phase has a large specific surface area and is prone to agglomeration during the mixing process. Agglomeration areas form large-sized pore defects, significantly reducing the strength of the matrix. Furthermore, the whiskers and fibers are oriented during molding and sintering, resulting in severe material anisotropy and a significant decrease in mechanical properties perpendicular to the fiber direction.

[0005] To address the aforementioned technical issues, existing technologies have developed a "particle gradation" scheme, in which coarse particles can form a skeleton, while fine particles fill the gaps between the coarse particles. This can effectively increase the bulk density of the powder, reduce internal pores and voids, and inhibit abnormal grain growth. Fine particles can also improve sintering activity, reduce the difficulty of densification in pressureless sintering, reduce sintering shrinkage, and prevent product cracking. However, simple particle gradation still suffers from low density, inconsistent sintering shrinkage rates between coarse and fine particles, and poor interfacial compatibility, limiting its ability to improve fracture toughness. Simple particle gradation can only control the morphology of matrix particles, without significant improvement in grain boundary softening, interfacial stress release, or high-temperature strength at high temperatures, and cannot be adapted to ultra-high temperature conditions. Summary of the Invention

[0006] To address the technical problems existing in the prior art, this invention provides a method for preparing particle-graded reinforced SiC ceramics, which improves interfacial compatibility, enhances the fracture toughness of the product, reduces sintering shrinkage, and enhances high-temperature resistance.

[0007] To address the aforementioned technical problems, the present invention adopts the following technical solution: A method for preparing particle-graded reinforced SiC ceramics includes silicon carbide gradation, coating, preparation of shaped powder, and sintering. The specific operations are as follows: 1. Silicon carbide gradation Silicon carbide powder was graded to obtain mixed silicon carbide, consisting of coarse, medium, and fine particles. The coarse particles had a diameter of 12-16 μm, the medium particles had a diameter of 3-5 μm, and the fine particles had a diameter of 0.3-0.7 μm. The mass ratio of coarse, medium, and fine particles was 4.8-5.8:2.3-3.2:1.3-2.2. Mixed silicon carbide was added to anhydrous ethanol, and polyethylene glycol 600 was added for ball milling. The ball milling speed was 320-350 rpm and the ball milling time was 4-6 h. After ball milling, the mixture was vacuum dried at 70-80℃ for 12-14 h to obtain graded silicon carbide. The mass ratio of the mixed silicon carbide, anhydrous ethanol, and polyethylene glycol 600 is 100:200-240:1.5-2.0.

[0008] 2. Covering Add hafnium nitrate and zirconium nitrate to anhydrous ethanol, stir at room temperature for 10-15 min, then add lanthanum nitrate and continue stirring for 10-15 min. After dissolving evenly, continue stirring for 30-35 min to obtain the precursor mixture. The precursor mixture has a total concentration of three metal ions of 0.15-0.2 mol / L, wherein the molar ratio of lanthanum, hafnium and zirconium ions is 5-5.5:2.5-3.5:1.5-2.5; Graded silicon carbide was added to a precursor mixture of 5-7 times its mass and ultrasonically dispersed for 25-30 minutes at an ultrasonic power of 120-140W and an ultrasonic frequency of 36-40kHz. After ultrasonication, the temperature was raised to 55-60℃, and 22-25wt% ammonia solution was added to adjust the pH to 8.5-9.0. The mixture was stirred and reacted for 2.0-2.3 hours. After centrifugation, the mixture was filtered and washed, and then vacuum dried at 70-75℃ for 10-12 hours. After cooling to room temperature, the mixture was placed in a calcination furnace and calcined at 570-600℃ for 2.0-2.2 hours under a nitrogen atmosphere. After natural cooling to room temperature, coated silicon carbide was obtained.

[0009] 3. Preparation of molded powder Coated silicon carbide, nano-sheet hexagonal boron nitride, and nano boron carbide are mixed and stirred evenly. Then, dodecyltrimethylammonium chloride is added and ball milled at a speed of 200-230 rpm for 1.5-2.0 h. After ball milling, shaped powder is obtained. The mass ratio of coated silicon carbide, nanosheet hexagonal boron nitride, nano boron carbide, and dodecyltrimethylammonium chloride is 100:2-4:0.5-0.6:0.15-0.20. The nanosheet-shaped hexagonal boron nitride has a diameter of 50-80 nm and a thickness of 5-10 nm. The particle size of the boron carbide nanoparticles is 300-350 nm; The particle size of the nano-carbon black is 80-100 nm; The lanthanum oxide has a particle size of 200-260 nm.

[0010] 4. Molding and calcination The powder is placed into a mold for dry pressing at a pressure of 20-25 MPa to obtain a preliminary blank. Then, it is subjected to cold isostatic pressing at 200-210 MPa for 5-6 minutes to obtain a blank. The green body is placed in a sintering furnace, and under a nitrogen atmosphere, the temperature is increased to 580-610℃ at a rate of 4-5℃ / min and held for 55-60min. Then, the temperature is increased to 1440-1470℃ at a rate of 6-8℃ / min and held for 55-60min. Finally, the temperature is increased to 1840-1850℃ at a rate of 2-3℃ / min and held for 120-130min. After naturally cooling to room temperature, particle-graded reinforced SiC ceramic is obtained.

[0011] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. This invention employs a three-level gradient gradation of silicon carbide particles. Coarse particles construct a rigid framework, while medium and fine particles fill the gaps, reducing the original packing porosity of the powder. Combined with polyethylene glycol 600, particle agglomeration is prevented, and particle dispersion is promoted, resulting in a high-density, uniformly dispersed graded silicon carbide powder. This reduces shrinkage and large-sized pores from the source. In the coating step, metal nitrates are co-precipitated with ammonia to form a La(OH)3-Hf(OH)4-Zr(OH)4 film on the surface of silicon carbide particles. After high-temperature calcination, a La2O3-HfO2-ZrO2 composite oxide nano-coating layer is obtained, which can significantly reduce sintering density, inhibit abnormal growth of silicon carbide grains, significantly improve fracture toughness, and enhance high-temperature stability. Then, it is mixed with boron nitride nanosheets and other auxiliary components to obtain a dense silicon carbide ceramic. 2. The particle-graded reinforced SiC ceramic prepared by this invention has a density of 98.5-99.2%; 3. The particle-graded reinforced SiC ceramic prepared by this invention has a linear shrinkage rate of 6.5-7.6%; 4. The particle-graded reinforced SiC ceramic prepared by this invention has a flexural strength of 503-517 MPa and a fracture toughness of 6.2-6.5 MPa·m. 1 / 2 ; After 10 cycles of thermal cycling, the flexural strength is 475-497 MPa, and the fracture toughness is 5.8-6.2 MPa·m. 1 / 2 . Detailed Implementation

[0012] To provide a clearer understanding of the technical features, objectives, and effects of the present invention, specific embodiments of the present invention are now described.

[0013] Example 1 1. Silicon carbide gradation Silicon carbide powder was graded to obtain mixed silicon carbide, consisting of coarse, medium, and fine particles. The coarse particles had a diameter of 16 μm, the medium particles had a diameter of 5 μm, and the fine particles had a diameter of 0.7 μm. The mass ratio of coarse, medium, and fine particles was 5.8:2.3:1.9. 100g of mixed silicon carbide was added to 240g of anhydrous ethanol, and 2.0g of polyethylene glycol 600 was added for ball milling. The ball milling speed was 350rpm and the ball milling time was 64h. After the ball milling was completed, the mixture was vacuum dried at 80℃ for 12h to obtain graded silicon carbide.

[0014] 2. Covering Hafnium nitrate and zirconium nitrate were added to anhydrous ethanol and stirred at room temperature for 15 min. Lanthanum nitrate was then added and stirred for another 15 min. After the mixture was dissolved evenly, it was stirred for another 35 min to obtain the precursor mixture. The precursor mixture has a total concentration of 0.2 mol / L for the three metal ions, wherein the molar ratio of lanthanum, hafnium, and zirconium ions is 5.3:2.8:1.9. Graded silicon carbide was added to a precursor mixture of 7 times its mass and ultrasonically dispersed for 30 min at a power of 140 W and a frequency of 40 kHz. After ultrasonication, the temperature was raised to 60 °C, and 25 wt% ammonia solution was added to adjust the pH to 9.0. The mixture was stirred and reacted for 2.3 h. After centrifugation, the mixture was filtered and washed, and then vacuum dried at 75 °C for 10 h. After cooling to room temperature, the mixture was placed in a calcination furnace and calcined at 600 °C for 2.2 h under a nitrogen atmosphere. After natural cooling to room temperature, coated silicon carbide was obtained.

[0015] 3. Preparation of molded powder 100g of coated silicon carbide, 4g of nano-sheet hexagonal boron nitride, and 0.6g of nano boron carbide were mixed and stirred evenly. Then, 0.20g of dodecyltrimethylammonium chloride was added, and the mixture was ball-milled at 230 rpm for 2.0 hours. After ball milling, the shaped powder was obtained. The nanosheet-shaped hexagonal boron nitride has a diameter of 80 nm and a thickness of 10 nm. The particle size of the boron carbide nanoparticles is 350 nm. The particle size of the nano-carbon black is 100 nm; The lanthanum oxide has a particle size of 260 nm.

[0016] 4. Molding and calcination The powder is placed into a mold for dry pressing at a pressure of 25 MPa to obtain a blank. Then, it is subjected to cold isostatic pressing at 210 MPa for 6 minutes to obtain a blank. The green body was placed in a sintering furnace and heated to 610°C at a rate of 5°C / min under a nitrogen atmosphere. The temperature was held for 60 min, then increased to 1470°C at a rate of 8°C / min and held for 60 min. The temperature was then increased to 1850°C at a rate of 3°C / min and held for 130 min. After natural cooling to room temperature, particle-graded reinforced SiC ceramic was obtained.

[0017] Example 2 1. Silicon carbide gradation Silicon carbide powder was graded to obtain mixed silicon carbide, which consisted of coarse particles, medium particles, and fine particles. The coarse particles had a particle size of 14 μm, the medium particles had a particle size of 4 μm, and the fine particles had a particle size of 0.5 μm. The mass ratio of coarse particles, medium particles, and fine particles was 5:3:2. 100g of mixed silicon carbide was added to 220g of anhydrous ethanol, and 1.8g of polyethylene glycol 600 was added for ball milling. The ball milling speed was 340rpm and the ball milling time was 5h. After ball milling, the mixture was vacuum dried at 75℃ for 13h to obtain graded silicon carbide.

[0018] 2. Covering Hafnium nitrate and zirconium nitrate were added to anhydrous ethanol and stirred at room temperature for 13 min. Lanthanum nitrate was then added and stirred for another 13 min. After the mixture was dissolved evenly, it was stirred for another 32 min to obtain the precursor mixture. The precursor mixture has a total concentration of 0.17 mol / L for the three metal ions, wherein the molar ratio of lanthanum, hafnium and zirconium ions is 5:3:2. Graded silicon carbide was added to a precursor mixture of 6 times its mass and ultrasonically dispersed for 28 min at a power of 130 W and a frequency of 38 kHz. After ultrasonication, the temperature was raised to 57 °C, and 23 wt% ammonia solution was added to adjust the pH to 8.7. The mixture was stirred and reacted for 2.2 h. After centrifugation, the mixture was filtered and washed, and then vacuum dried at 73 °C for 12 h. After cooling to room temperature, the mixture was placed in a calcination furnace and calcined at 580 °C for 2.2 h under a nitrogen atmosphere. After natural cooling to room temperature, coated silicon carbide was obtained.

[0019] 3. Preparation of molded powder 100g of coated silicon carbide, 3g of nano-sheet hexagonal boron nitride, and 0.6g of nano boron carbide were mixed and stirred evenly. Then, 0.17g of dodecyltrimethylammonium chloride was added and ball milled at 220 rpm for 1.8 hours. After ball milling, the shaped powder was obtained. The nanosheet-shaped hexagonal boron nitride has a diameter of 70 nm and a thickness of 7 nm. The particle size of the boron carbide nanoparticles is 330 nm; The particle size of the nano-carbon black is 90 nm; The lanthanum oxide has a particle size of 240 nm.

[0020] 4. Molding and calcination The powder to be formed is placed into a mold for dry pressing at a pressure of 23 MPa to obtain a blank. Then, it is subjected to cold isostatic pressing at 205 MPa for 6 minutes to obtain a blank. The green body was placed in a sintering furnace and heated to 600°C at a rate of 5°C / min under a nitrogen atmosphere. The temperature was held for 57 min, then increased to 1450°C at a rate of 7°C / min and held for 58 min. The temperature was then increased to 1845°C at a rate of 3°C / min and held for 125 min. After natural cooling to room temperature, particle-graded reinforced SiC ceramic was obtained.

[0021] Example 3 1. Silicon carbide gradation Silicon carbide powder was graded to obtain mixed silicon carbide, consisting of coarse, medium, and fine particles. The coarse particles had a diameter of 12 μm, the medium particles had a diameter of 3 μm, and the fine particles had a diameter of 0.3 μm. The mass ratio of coarse, medium, and fine particles was 4.8:3.2:2. 100g of mixed silicon carbide was added to 200g of anhydrous ethanol, and 1.5g of polyethylene glycol 600 was added for ball milling. The ball milling speed was 320rpm and the ball milling time was 4h. After ball milling, the mixture was vacuum dried at 70℃ for 14h to obtain graded silicon carbide.

[0022] 2. Covering Hafnium nitrate and zirconium nitrate were added to anhydrous ethanol and stirred at room temperature for 10 min. Lanthanum nitrate was then added and stirred for another 10 min. After the mixture was dissolved evenly, it was stirred for another 30 min to obtain the precursor mixture. The precursor mixture has a total concentration of 0.15 mol / L for the three metal ions, wherein the molar ratio of lanthanum, hafnium, and zirconium ions is 5.5:2.5:2. Graded silicon carbide was added to a precursor mixture of 5 times its mass and ultrasonically dispersed for 25 min at a power of 120 W and a frequency of 36 kHz. After ultrasonication, the temperature was raised to 55 °C, and 22 wt% ammonia solution was added to adjust the pH to 8.5. The mixture was stirred and reacted for 2.0 h. After centrifugation, the mixture was filtered and washed, vacuum dried at 70 °C for 12 h, cooled to room temperature, and then placed in a calcination furnace. Under a nitrogen atmosphere, the mixture was calcined at 570 °C for 2.0 h and then naturally cooled to room temperature to obtain coated silicon carbide.

[0023] 3. Preparation of molded powder 100g of coated silicon carbide, 2g of nano-sheet hexagonal boron nitride, and 0.5g of nano boron carbide were mixed and stirred evenly. Then, 0.15g of dodecyltrimethylammonium chloride was added and ball milled at 200 rpm for 1.5 hours. After ball milling, the shaped powder was obtained. The nanosheet-shaped hexagonal boron nitride has a diameter of 50 nm and a thickness of 5 nm. The particle size of the boron carbide nanoparticles is 300 nm; The particle size of the nano-carbon black is 80 nm; The lanthanum oxide has a particle size of 200 nm.

[0024] 4. Molding and calcination The powder is placed into a mold for dry pressing at a pressure of 20 MPa to obtain a blank. Then, it is subjected to cold isostatic pressing at 200 MPa for 5 minutes to obtain a blank. The green body was placed in a sintering furnace and heated to 580°C at a rate of 4°C / min under a nitrogen atmosphere. The temperature was held for 55 min, then increased to 1440°C at a rate of 6°C / min and held for 55 min. The temperature was then increased to 1840°C at a rate of 2°C / min and held for 120 min. After natural cooling to room temperature, particle-graded reinforced SiC ceramic was obtained.

[0025] Comparative Example The changes made in Example 2 are as follows: The silicon carbide gradation step is omitted, and the graded silicon carbide is replaced in equal amounts with untreated silicon carbide particles with a particle size of 4 μm. The coating step involves mixing graded silicon carbide with lanthanum oxide, hafnium oxide, and zirconium oxide, stirring until homogeneous, to obtain coated silicon carbide. The mass ratio of the graded silicon carbide, lanthanum oxide, hafnium oxide, and zirconium oxide is 100:2.0:1.0:1.0; The rest of the operations are exactly the same.

[0026] Performance testing The particle size distribution reinforced SiC ceramics prepared in Examples 1-3 and the comparative examples were subjected to the following performance tests, and the results are as follows:

[0027] The particle-graded reinforced SiC ceramics prepared in Examples 1-3 and the comparative example were subjected to temperature increases to 1500°C at a rate of 10°C / min and held for 12 hours in air. The temperature was then decreased to 10°C at a rate of 30°C / min and held for 12 hours. This treatment was repeated as one cycle for 10 consecutive cycles. The flexural strength and fracture toughness were then assessed, and the results are as follows:

[0028] The comparative example omits the gradient gradation and directly uses silicon carbide particles with a diameter of 4μm. The packing density of silicon carbide particles is reduced, and there are a large number of pores between the particles. During the sintering process, the particle rearrangement and compression space is large, and the shrinkage rate increases. When it is directly mixed with rare earth oxides, local oxide agglomeration occurs, and the grains grow abnormally. This will reduce the toughness and strength of the product, and it is prone to cracking during thermal cycling, affecting the overall performance of the product.

[0029] Unless otherwise stated, all percentages used in this invention are mass percentages.

[0030] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing particle-graded reinforced SiC ceramics, characterized in that, This includes steps such as silicon carbide gradation, coating, preparation of shaped powder, and calcination. The silicon carbide gradation step includes gradient gradation of silicon carbide powder to obtain mixed silicon carbide, which consists of coarse particles, medium particles, and fine particles, wherein the particle size of the coarse particles is 12-16 μm, the particle size of the medium particles is 3-5 μm, and the particle size of the fine particles is 0.3-0.7 μm, and the mass ratio of coarse particles, medium particles, and fine particles is 4.8-5.8:2.3-3.2:1.3-2.2; The coating step is as follows: hafnium nitrate and zirconium nitrate are added to anhydrous ethanol and stirred at room temperature for 10-15 min. Lanthanum nitrate is then added and stirred for another 10-15 min until it is evenly dissolved. The mixture is then stirred for another 30-35 min to obtain a precursor mixture. Graded silicon carbide is added to 5-7 times its mass of the precursor mixture and ultrasonically dispersed for 25-30 min. The temperature is raised to 55-60℃, and an ammonia solution is added to adjust the pH to 8.5-9.

0. The mixture is stirred for 2.0-2.3 h. After centrifugation, the mixture is filtered, washed, dried, and cooled to room temperature. It is then placed in a calcination furnace and calcined at 570-600℃ for 2.0-2.2 h under a nitrogen atmosphere. After natural cooling to room temperature, coated silicon carbide is obtained.

2. The method for preparing particle-graded reinforced SiC ceramics according to claim 1, characterized in that, The silicon carbide gradation step further includes adding mixed silicon carbide to anhydrous ethanol, adding polyethylene glycol 600 for ball milling, ball milling speed of 320-350 rpm, ball milling time of 4-6 h, and after ball milling, vacuum drying at 70-80℃ for 12-14 h to obtain graded silicon carbide. The mass ratio of the mixed silicon carbide, anhydrous ethanol, and polyethylene glycol 600 is 100:200-240:1.5-2.

0.

3. The method for preparing particle-graded reinforced SiC ceramics according to claim 1, characterized in that, In the coating step, the total concentration of the three metal ions in the precursor mixture is 0.15-0.2 mol / L, wherein the molar ratio of lanthanum, hafnium and zirconium ions is 5-5.5:2.5-3.5:1.5-2.

5.

4. The method for preparing particle-graded reinforced SiC ceramics according to claim 1, characterized in that, The steps for preparing the shaped powder are as follows: coated silicon carbide, nano-sheet hexagonal boron nitride, and nano boron carbide are mixed and stirred evenly. Then, dodecyltrimethylammonium chloride is added and ball milled at a speed of 200-230 rpm for 1.5-2.0 h. After ball milling, the shaped powder is obtained.

5. The method for preparing particle-graded reinforced SiC ceramics according to claim 4, characterized in that, The mass ratio of coated silicon carbide, nanosheet hexagonal boron nitride, nano boron carbide, and dodecyltrimethylammonium chloride is 100:2-4:0.5-0.6:0.15-0.

20.

6. The method for preparing particle-graded reinforced SiC ceramics according to claim 4, characterized in that, The nanosheet-shaped hexagonal boron nitride has a diameter of 50-80 nm and a thickness of 5-10 nm. The particle size of the boron carbide nanoparticles is 300-350 nm; The particle size of the nano-carbon black is 80-100 nm; The lanthanum oxide has a particle size of 200-260 nm.

7. The method for preparing particle-graded reinforced SiC ceramics according to claim 1, characterized in that, The molding and calcination step is as follows: the molding powder is placed into a mold for dry pressing molding at a molding pressure of 20-25 MPa to obtain a preliminary blank, and then subjected to cold isostatic pressing molding treatment at 200-210 MPa for 5-6 minutes to obtain a blank. The green body is placed in a sintering furnace, and under a nitrogen atmosphere, the temperature is increased to 580-610℃ at a rate of 4-5℃ / min and held for 55-60min. Then, the temperature is increased to 1440-1470℃ at a rate of 6-8℃ / min and held for 55-60min. Finally, the temperature is increased to 1840-1850℃ at a rate of 2-3℃ / min and held for 120-130min. After naturally cooling to room temperature, particle-graded reinforced SiC ceramic is obtained.